Network-Based Selection of Candidate Markers and Assays to Assess the Impact of Oral Immune Interventions on Gut Functions - Meijerink, Marjolein; van den Broek, Tim J.; Dulos, Remon; Garthoff, Jossie; Knippels, Léon; Knipping, Karen; Harthoorn, Lucien; Houben, Geert; Verschuren, Lars; van Bilsen, Jolanda (Frontiers in Immunology, 2019)
To assess the safety and efficacy of oral immune interventions, it is important and regulatory required to assess the impact of those interventions not only on the immune system, but also on other organs, such as the gut as porte d’entrée. Despite clear indications that the immune system interacts with several physiological functions of the gut, it is still unknown which pathways and molecules are crucial to assess the impact of nutritional immune interventions on gut functioning. Here we used a network-based systems biology approach to clarify the molecular relationships between immune system and gut functioning and to identify crucial biomarkers to assess effects on gut functions upon nutritional immune interventions. First, the different gut functionalities were categorized based on literature and EFSA guidance documents. Moreover, an overview of the current assays and methods to measure gut function was generated. Secondly, gut-function related biological processes and adverse events were selected and subsequently linked to the physiological functions of the GI tract. Thirdly, database terms and annotations from Gene ontology database and Comparative Toxicogenomics Database (CTD) were selected that were related to the previously selected gut-function related processes. Next, the database terms and annotations were used to identify the pathways and genes involved in those gut functionalities. In parallel, information from CTD was used to identify immune disease related genes. The resulting lists of genes of both gut and immune functions showed an overlap of 753 genes out of 1296 gut-function related genes indicating the close gut-immune relationship. Using bioinformatics enrichment tools DAVID and Panther, the identified gut-immune markers were predicted to be involved in motility, barrier function, vitamin and fat digestion and absorption, regulation of the digestive system and gastric acid, and protection from injurious or allergenic material. Concluding, here we provide a promising systems biology approach to identify genes that help to clarify the relationships between immune system and gut functioning, with the aim to identify candidate biomarkers to monitor in safety and efficacy assays upon nutritional immune interventions. This knowledge helps to optimize future study designs to predict effects of nutritional immune intervention on gut functionalities.